The magnitude of gender-based violence, health consequences, and associated factors among women living in post-war woredas of North Shewa zone, Amhara, Ethiopia, 2022 - Asefa, Eyosiyas Yeshialem; Haile, Assalif Beyene; Mohamed, Osman Yimer; Berhanu, Dagimawit (Frontiers in Global Women's Health, 2024)
Background: Gender-based violence (GBV) is a pervasive global public health concern and a violation of human rights, particularly pronounced in conflict settings where it is often used as a tool of warfare to instill fear and control populations.Objective: Assessment of Magnitude, Associated Factors, and Health Consequences of GBV among women living in war-affected woredas of North Shewa zone, Ethiopia, 2022 Methods: A community-based cross-sectional study was conducted, involving 845 randomly selected women living in conflict zones. Data on GBV experiences over the previous 3 months were collected through interviewer-administered questionnaires developed from literature review. The collected data underwent validation, entry into EPI data, and analysis using SPSS. Findings are summarized using descriptive statistics, AOR and 95% confidence interval.The magnitude of GBV in this study was (490, 58.0%) where, (466, 55.0%) psychological violence, (254, 30.1%) physical violence, and ( 135, 16.0%) reported sexual violence. A majority of the physical violence, (161, 63.4%), occurred during conflict period, with (143, 56.3%) of these cases involving armed forces, and (161, 63.4%) women experiencing physical violence in their homes. Urban Residence AOR=2.65, CI [1.82-3.89], Educational status of Secondary education AOR=0.33 CI [0.19-0.57, and ≥College AOR=0.17 CI [0.09-0.35], Occupation of Housewife AOR=1.88 CI [1.20-2.94], Private employee AOR=6.95 CI [3.70-13.04], Gov't employee AOR=5.80 CI [2.92-11.50], and others (Students) AOR= 3.46 CI [1.98-6.01], Ever had sexual intercourse AOR=0.46 CI [0.25-0.83], Have heard about SRH AOR=0.59 CI [0.40-0.89], Have had previous GBV exposure AOR=0.24 CI [0.15-0.38], having a previous history of sexual violence AOR=0.30 CI [0.16-0.57], and Number of sexual partner AOR=1 ] were identified to be associated factors of GBV in our study area. The most commonly reported consequences of GBV were Anxiety, depression, physical injuries, self-blame, women had school dropout, and abortion.The study reveals a higher prevalence of GBV, resulting in profound physical, social, mental, and reproductive health challenges for survivors. To address this, multi-sectoral cooperation is advised to enhance women's empowerment, access to information, and psycho-social support in affected areas. Furthermore, national policymakers are urged to implement preventive measures during conflict and establish legal mechanisms to ensure accountability for perpetrators.